Effectiveness of Psycholinguistic Approaches in Improving Students’ Achievements in Writing in the Online Distance Learning Setting: A Case Study on Grade Eleven Students in the UAE - EMARA, TAREK MAHMOUD IBRAHIM (2023)
Because of the Covid-19 pandemic, Online Distance Learning (ODL) has become an important learning tool that needs more attention from educationalists to be effectively used to deliver the English language to second language learners. This requires English language teachers (ELTs) to adopt valid methodological approaches and adapt suitable strategies to help improve their teaching practices in ODL classrooms, which may be applicable in other language teaching contexts. This study is a contribution to our knowledge of how to effectively employ psycholinguistic approaches in the ODL setting to improve students’ achievements in the English Language Writing Skill (ELWS). To investigate and explore its effectiveness in improving students’ ELWS achievements in the ODL setting. A mixed-methods approach was employed, using the pretest-posttests, and classroom observations during 8-week intervention on an experimental group treated by implementing the proposed psycholinguistic framework and a control group that was taught conventionally. A close-ended questionnaire was also employed to explore ELTs’ perceptions of psycholinguistic approaches and elicit their suggestions to implement them more effectively and figure out some solutions to any upcoming ODL challenges. Results from the pretest-posttests and findings from the classroom observations show that there is a difference in students’ ELWS achievements in favor of the experimental group. Results from the questionnaire show that ELTs need to enrich their knowledge to be skillful enough to master the ODL setting.